2020
DOI: 10.1002/smj.3252
|View full text |Cite
|
Sign up to set email alerts
|

Reexamining investor reaction to covert corporate political activity: A replication and extension of Werner (2017)

Abstract: Exploiting a whistleblower's leak of the American Legislative Exchange Council's (ALEC) corporate sponsors, we quasi-replicate and extend Werner's (2017) event study of investor reaction to covert corporate political activity (CPA). Werner found that investors reacted positively to the accidental disclosure of covert ties to the Republican Governors Association. In contrast, when we apply the same research design to the ALEC leak, we find that, on

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 30 publications
(26 citation statements)
references
References 49 publications
0
25
0
Order By: Relevance
“…In particular, we argue it is important to view lobbying breadth as an insurance or risk management tool by focusing on the preventive or buffering goals of lobbying, which are often overlooked (Hillman et al, 2004), as well as its role in helping to generate political capital (Kim, 2019). Thus, even though some stakeholders may approach firm lobbying activity with suspicion based upon the perceived legitimacy or “acceptability” of it (Jia, 2018; Minefee et al, 2020), when considered legitimate, a broad risk management view of lobbying by firms may suggest important positive benefits from this nuanced aspect of firm political behavior. Particularly, this view of lobbying moves beyond the primary focus of the CPA literature on the benefits firms accrue from such actions (Mellahi et al, 2016) and emphasizes how the breadth of CPA may provide additional insight above and beyond the amount that firms expend or the simple fact they engage in CPA at all.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
See 2 more Smart Citations
“…In particular, we argue it is important to view lobbying breadth as an insurance or risk management tool by focusing on the preventive or buffering goals of lobbying, which are often overlooked (Hillman et al, 2004), as well as its role in helping to generate political capital (Kim, 2019). Thus, even though some stakeholders may approach firm lobbying activity with suspicion based upon the perceived legitimacy or “acceptability” of it (Jia, 2018; Minefee et al, 2020), when considered legitimate, a broad risk management view of lobbying by firms may suggest important positive benefits from this nuanced aspect of firm political behavior. Particularly, this view of lobbying moves beyond the primary focus of the CPA literature on the benefits firms accrue from such actions (Mellahi et al, 2016) and emphasizes how the breadth of CPA may provide additional insight above and beyond the amount that firms expend or the simple fact they engage in CPA at all.…”
Section: Conceptual Backgroundmentioning
confidence: 99%
“…While the growing body of research on how firms allocate CPA suggests generally there may be benefits to widening breadth (see Minefee, McDonnell, & Werner, 2020, for a discussion of some exceptions), extant work focuses almost entirely on the outcomes of such actions (e.g., government contracts and firm performance in Ridge et al, 2017; stock returns in Cooper et al, 2010; survival and growth in Zheng, Singh, & Mitchell, 2015). Little focus has been given to understanding what drives firms’ CPA breadth, however, raising important questions for our knowledge of the topic.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This was especially true when the firm previously engaged in CPA or they were in heavily regulated industries, but it was viewed negatively if the firm had been previously asked by shareholder resolution to reveal all of its political investments. In an extension of this work, Minefee, McDonnell, and Werner (2021) found that when firms' dark money investments were targeted toward controversial sociopolitical issues, investor reactions were negative. Firms' participation in CSR mitigated this relationship.…”
Section: Bands Firm Experience and Opportunitymentioning
confidence: 78%
“…They suggest that firms do this as part of their effort to manage general public stakeholders while still influencing the content and intensity of regulation by the government via CPA. We also have some evidence of stakeholder response to covert CPA after the revelation of dark money contributions of firms (Werner, 2017;Minefee, McDonnell, & Werner, 2021). One of the problems of doing research on covert CPA is that by definition, firms are attempting to conceal these actions, and therefore, information may not be easily available in the public domain.…”
Section: Covert Cpamentioning
confidence: 96%